Dishonesty as a signal of trustworthiness: Honesty-Humility and trustworthy dishonesty - Karolina A. Ścigała (Royal Society Open Science, 2020)
Trustworthiness is a foundation of well-functioning relationships and societies, and thus often perceived as a socially normative behaviour. Correspondingly, a broad array of research found that people tend to act in a trustworthy way and signal their trustworthiness to others, and that trustworthiness is rewarded. Herein, we explore whether this motivation to behave trustworthily can have socially undesirable effects in terms of leading to dishonesty targeted at fulfilling the trustor's expectations (i.e. trustworthy dishonesty). Furthermore, we examine how the basic trait of Honesty-Humility, which has consistently been found to be linked to both higher honesty and trustworthiness, relates to trustworthy dishonesty, where honesty and trustworthiness are at odds. Specifically, we conducted three pre-registered studies (N = 7080), introducing a novel behavioural game, the lying-trust game, where participants had a chance to lie to act trustworthily. In two studies, we found that, when offered ‘full trust’, participants high in Honesty-Humility (i.e. the top 10%) engaged in trustworthy dishonesty, i.e. lied in order to avoid maximizing their own incentive at the cost of minimizing the incentive of their trustor. This pattern was not present when the trustor offered minimal trust only, as well as among participants low in Honesty-Humility (i.e. the bottom 10%).